In search of quantum-limited contact resistance: understanding the intrinsic and extrinsic effects on the graphene–metal interface. (13th April 2016) - Nath, Anindya; Currie, Marc; Boyd, Anthony K; Wheeler, Virginia D; Koehler, Andrew D; Tadjer, Marko J; Robinson, Zachary R; Sridhara, Karthik; Hernandez, Sandra C; Wollmershauser, James A; Robinson, Jeremy T; Myers-Ward, Rachael L; et al.
Abstract: Owing to its two-dimensional structure, graphene is extremely sensitive to surface contamination. Conventional processing techniques inevitably modify graphene's intrinsic properties by introducing adsorbents and/or defects which limit device performance and understanding the intrinsic properties of graphene. Here we demonstrate femtosecond laser direct patterning of graphene microstructures, without the aid of resists or other chemicals, that enables us to study both intrinsic and extrinsic effects on the graphene–metal interface. The pulsed femtosecond laser was configured to ablate epitaxial graphene (EG) on a sub-micrometer scale and form a precisely defined region without damaging the surrounding material or substrate. The ablated area was sufficient to electrically isolate transfer length measurement structures and Hall devices for subsequent transport measurements. Using pristine and systematically contaminated surfaces, we found that Ni does not form bonds to EG synthesized on SiC in contrast to the well-known C–Ni bond formation for graphene synthesized on metals; known as end-contacting. Without end-contacting, the contact resistance ( R C ) of Ni to pristine and resist-contaminated EG are one and two orders of magnitude larger, respectively, than the intrinsic quantum limited contact resistance. The range of reported R C values is explained using carrier transmission probability, as exemplified by the Landauer–Büttiker model, which is dependent on the presence or absence of end-contacts and dopant/work-function mediated conduction. The model predicts the need for both end-contacts and a clean graphene–metal interface as necessary conditions to approach quantum limited contact resistance.